Tuning In‐Plane Wicking Properties of Hydrophilic Fibrous Membranes Using Hydrophobic Fibrous Cover Layers - Hongjie Wang; He Wang; Xin Jin; Hua Zhou; Hongxia Wang; Wenyu Wang; Fangtao Ruan; Quan Feng; Tong Lin (Advanced Materials Interfaces, 2023)
Abstract This study elucidates the effect of thin porous hydrophobic covering layers on the in‐plane wicking properties of a hydrophilic fibrous membrane. Polyacrylonitrile (PAN) fibrous membrane is used as the hydrophilic membrane model and poly(vinylidene fluoride‐hexafluoropropylene) (PVDF‐HFP) fibrous membranes as hydrophobic covers, both prepared by electrospinning. The vertical wicking height is measured to express the in‐plane wicking properties. The results show that the PVDF‐HFP fibrous layer profoundly impacted the in‐plane wicking properties. When the PVDF‐HFP layer is 5.00–7.05 µm in thickness, the PVDF‐HFP/PAN composite membranes show a directional water transport property. The wicking height is higher than the other composite membranes with either a thinner PVDF‐HFP layer (<5.00 µm), which causes a two‐way liquid transport, or a thicker PVDF‐HFP layer (>7.05 µm), which stops water permeation from both sides. Such a trend happened no matter whether the PVDF‐HFP layer covered one or both PAN membrane sides. The composite membranes with a PVDF‐HFP layer thicker than 7.05 µm show the smallest wicking height. By changing PVDF‐HFP layer thickness, the wicking height can be adjusted by 50–110%. Such thickness‐dependent wicking capability is novel, having not been reported in the previous literature. It comes from the combined action of hydrophobic and hydrophilic surfaces on water. The tunable wicking properties combined with the water‐absorbing and transport properties enabled the PVDF‐HFP/PAN fibrous membranes to exhibit different functions. They offer opportunities to develop novel “smart” membranes for various applications.